2022
DOI: 10.3389/feart.2022.1002366
|View full text |Cite
|
Sign up to set email alerts
|

Volatile trace metals deposited in ice as soluble volcanic aerosols during the 17.7.ka eruptions of Mt Takahe, West Antarctic Rift

Abstract: Volatile metals are emitted at significant rates as gases and particulates from volcanoes, although their speciation, bioreactivity and longevity during atmospheric transport are essentially unknown. Ice cores provide detailed yet largely unexplored long-term records of volcanogenic volatile metals in air and precipitation. Here we evaluate the source and speciation of volatile metals (cadmium, lead, bismuth, and thallium) in Antarctic ice cores from the massive, halogen-rich and sulfur-poor ∼17.7 ka eruptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…29 who used Tl to assess past volcanic emissions of heavy metals (Bi, lead, cadmium) in Antarctic ice during the Common Era and ref. 30 who propose that volatile metals from volcanic sources can be transported to nearby icecore sites (i.e., 400 km distance) as water soluble aerosols, forming metalhalogen complexes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 who used Tl to assess past volcanic emissions of heavy metals (Bi, lead, cadmium) in Antarctic ice during the Common Era and ref. 30 who propose that volatile metals from volcanic sources can be transported to nearby icecore sites (i.e., 400 km distance) as water soluble aerosols, forming metalhalogen complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Within Antarctic ice cores, a pronounced elevated halogen and metal enrichment lasting 192 years (~17.7 ka) was attributed to regional West Antarctic volcanism 23,30,48 . Mason et al 30 suggested that the long-lasting excessive deposition of these volatile species is indicative of a proximal eruption, with magma source chemistry, eruptive processes, and plume transport also contributing to the signature within the ice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation